Population biology : the evolution and ecology of populations - Hedrick, Philip W. (Boston : jones and Bartlett Publishers, 1984)
General Science
Keywords: Population biology; Evolution; Ecology; Population genetics; Population ecology; Ecological genetics; Evolutionary ecology